Loss of Growth Differentiation Factor 11 Shortens Telomere Length by Downregulating Telomerase Activity - Wang, Di-Xian; Zhu, Xu-Dong; Ma, Xiao-Ru; Wang, Li-Bin; Dong, Zhao-Jun; Lin, Rong-Rong; Cao, Yi-Na; Zhao, Jing-Wei (Frontiers in Physiology, 2021)
Maintenance of telomere length is essential to delay replicative cellular senescence. It is controversial on whether growth differentiation factor 11 (GDF11) can reverse cellular senescence, and this work aims to establish the causality between GDF11 and the telomere maintenance unequivocally. Using CRISPR/Cas9 technique and a long-term in vitro culture model of cellular senescence, we show here that in vitro genetic deletion of GDF11 causes shortening of telomere length, downregulation of TERT and TERC, the key enzyme and the RNA component for extension of telomere, and reduction of telomerase activity. In contrast, both recombinant and overexpressed GDF11 restore the transcription of TERT in GDF11KO cells to the wild type level. Furthermore, loss of GDF11 induced telomere shortening is likely caused by enhancing nuclear entry of SMAD2 which inhibits the transcription of TERT and TERC. Our results provide the first proof of a cause-and-effect evidence that endogenous GDF11 plays a causal role for proliferative cells to maintain telomere length, paving the way for potential rejuvenation of the proliferative cells, tissues and organs.